Does Customer Relationship Management Affects Customer Satisfaction? Analysis of Findings from Jordanian Commercial Banks (Global Journal of Management and Business Research, 2020)
The service industry has always more challenging and competitive because customers are constantly demanding more services for less money. This has shifted organizations strategic plans and goals towards customer orientation and satisfaction. The importance of retaining existing customers and expanding business is paramount. Hence, efforts are laid by all the firms towards maintaining sound relationship with customers. This process is known as CRM. Customer Relationship Management or CRM is a customer oriented strategy for creating, maintaining and expanding customer relationships.
Keywords: CRM; customer satisfaction; customer loyalty; banks